ADVANCED TECHNOLOGY OF LUMINOPHOR SCREENS FOR SOLID RADIOLUMINESCENT LIGHT SOURCES - E. V. Zelenina; E. A. Pechertseva; V. V. Bakhmetyev; M. M. Sychov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article observes different methods of coating the phosphor screens on the tritiated titanium matrices for creating the solid-state radioluminescent light sources (SRLS). Technology of SRLS is alternative to the existing technology of the gas-filled radioluminescent light sources. The main idea of SRLS is in bonding the working isotope (tritium) in the solid matrix and combining it with the phosphor. The key problem of SRLS is to provide the closest contact between the tritiated carrier matrix and phosphor screen. The basic requirements for the phosphor screens for SRLS would be the strength of fixation on the plate, uniformity and radiological and thermal stability. There have been made a comparison of various techniques of coating and fixing the phosphor screens by their effect on spectral and brightness characteristics of SRLS. The improved sol-gel technique of suspended sedimentation of phosphor screen from the potassium water glass binder solution was developed. The composition of the solution was established experimentally and we get the strong and uniform experimental prototypes of the glass coated phosphor screens of various thickness. The developed technology allows to deposit the strong and uniform phosphor coatings without using any additional dispersing agents. Screen thickness regulates by the amount of phosphor in the suspension. Also the optimal thickness of the phosphor screen, giving the maximum luminescence intensity was determined. The two laboratory prototypes of solid-state radioluminescent light sources were manufactured by coating the phosphor directly on the tritium β-source.